The Effectiveness of PECS in Improving Expressive Communication Skills among Second-Grade Students with Autism in Special Schools - Rustika Rustika; Heni Herlina; Annisa Purwanggi (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
Children with autism spectrum disorder often experience difficulties in expressive communication, which affect their ability to convey needs, initiate interactions, and express emotions, thereby impacting learning processes and social participation in school. One widely used approach is the Picture Exchange Communication System (PECS), a visual-based communication method that enables children to convey messages functionally through picture exchange. This study aims to examine the effectiveness of PECS in improving expressive communication skills among second-grade students with autism at SLBN Sidomulyo. A quantitative approach with a Single Subject Research (SSR) design using an A–B–A pattern was employed. Data were collected through structured observation and analyzed using visual analysis within and across conditions. The results show an increase in expressive communication skills from 20% in the initial baseline phase to 50% during intervention, and 80% in the follow-up baseline phase. The absence of significant data overlap indicates consistent behavioral change after the intervention. These findings confirm that PECS is effective and produces sustained improvements.